Digital Literacy in Multicultural Islamic Education: Evolution, Trends, and Systematic Mapping - Hanip Hidayatulloh; Ishmah Afiyah (Walidem Institute and Publishing (WIP), 2025)
Objective: This study aims to investigate the evolution of digital literacy in multicultural Islamic education by mapping its development, dominant themes, and academic contributions from 2011 to 2025. The central objective is to identify how digital literacy has been conceptualized and integrated within Islamic educational contexts, particularly in relation to multicultural values and global educational transformations. Theoretical framework: This research is grounded in the interdisciplinary framework that connects digital literacy, multiculturalism, and Islamic pedagogy, positioning digital skills not only as technical competencies but also as ethical and cultural capital aligned with Islamic values. Literature review: The literature review highlights growing scholarly attention to the intersection of digital literacy and Islamic education, with emerging themes including religious moderation, online pedagogy, technological adaptation in teaching, and the role of artificial intelligence. However, existing works often remain fragmented, lacking a comprehensive synthesis that situates these issues within a broader global and multicultural perspective. Method: The study employs a Systematic Literature Review (SLR) combined with bibliometric analysis of Scopus-indexed publications, applying the PRISMA protocol for article selection. Twenty-six relevant studies were identified and analyzed using VOSviewer and R (Bibliometrix) software. Quantitative mapping explored publication trends, collaboration networks, and keyword co-occurrence, while qualitative synthesis examined thematic clusters and theoretical contributions. Results: Findings indicate a significant rise in publications since 2020, with Indonesia emerging as a central hub of research in this field. Dominant themes include integrating digital literacy with Islamic values, strengthening religious moderation, preparing teachers and lecturers for technological change, expanding online learning practices, and exploring artificial intelligence as a pedagogical tool. Implications: The implications of this study are twofold: theoretically, it advances the conceptualization of digital literacy in Islamic education as an interdisciplinary and multicultural construct; practically, it offers insights for curriculum development, educational policies, and strategies to strengthen adaptive digital competencies. Novelty: The novelty of this research lies in its systematic mapping of digital literacy within multicultural Islamic education, providing the first comprehensive overview that bridges bibliometric evidence with thematic synthesis across a global and interdisciplinary landscape.